A case series of morbid COPD exacerbations during immune checkpoint inhibitor therapy in cancer patients. (2021) - Nair, Viswam S.; Eaton, Keith; McGarry Houghton, A.
Abstract: Background: Immune checkpoint inhibitor therapy is rapidly becoming front line adjuvant or primary therapy in a number of solid cancer types. Since many of these cancers are a result of tobacco smoking, a large number of these patients will have underlying comorbid conditions attributed to smoking such as Chronic Obstructive Pulmonary Disease (COPD). The effect of immune checkpoint inhibitor therapy on COPD is not well documented, and COPD exacerbations are not currently considered a pulmonary associated immune checkpoint inhibitor toxicity in current guidelines. Case presentation: We describe and summarize here a series of patients with prolonged and severe COPD exacerbations upon the initiation of immune checkpoint inhibitor therapy for cancers of the skin and lung without radiographic evidence of pneumonitis. Conclusions: COPD exacerbation from immune checkpoint inhibitor is not reported in the literature and is associated with prolonged and severe episodes without radiographic evidence of pneumonitis. Awareness of this potential morbid toxicity and research efforts to understand its etiology are required.